Insights into the behavior and kinetics of purun tikus degradation during slow pyrolysis - Farobie, Obie; Amrullah, Apip (PERTETA, 2023)
Purun tikus (Elocharis dulcis), a type of wetland biomass feedstock, is a challenge to the swamp ecosystem as it contributes to pollution in the area. Hence, integrating the use of purun tikus as a source of bioenergy, particularly in the form of bio-oil, is of the highest priority. Nevertheless, there is a lack of research on the degradation rate of purun tikus conversion to bio-oil through pyrolysis. Thus, this study aims to evaluate the rate of destruction of purun tikus in the process of conversion into bio-oil via pyrolysis. In the experiment, a batch reaction vessel was used to carry out slow pyrolysis at temperatures ranging from 300 to 500 °C, and the reaction times ranged from 60 to 120 min. By assuming a first-order process and using the Arrhenius equation, it was possible to figure out the activation energy and the preexponential factort. To determine whether purun tikus destroyed during pyrolysis, an activation energy of 43.317 kJ mol-1 and a pre-exponential factor of 0.351 s-1 were identified.